(untitled) (icade. Journal of the Faculty of Law at Universidad Pontificia Comillas, 2017)
In 2012 the Constitutional Court resolved the appeal of unconstitutionality against the Law through which right to marry to the same sex had been recognized in our legal system. This Judgment has had a great impact on our constitutional system, which goes beyond what was specific object of debate (the concept of marriage), proposing a new way of interpreting the rights that may suppose that we are in front of a new Constitutional Court which makes of its constitutional function a true expression of judicial activism. In this paper we analyze if this is really so and the future effects of that sentence in our constitutional system of rights and freedoms.